Region of Interest Extraction using Colour Based Methods on the CUAVE Database - HARTE, NAOMI (My University, 2009)
Region of interest (ROI) extraction is an important step in deriving vi- sual features for an audio-visual speech recognition system. Colour based segmentation oers the potential of computationally inexpensive algorithms for ROI selection. This paper presents a comparative study of two colour based techniques, one using hue and accumulated dierence, the other chrominance. Results are presented for the CUAVE database. The two methods achieved 69% and 72% correct ROI extraction. The exper- iment prompted investigation of a new method using a chrominance based accumulated dierence image. The new method achieved 79% correct ROI identication. The overall results suggest that a dual approach using chrominance to locate the mouth region and only employing an accumulated dierence image when signicant motion is not present would oer good robustness with lower computational cost.
IET Irish Signals and Systems Conference ISSC
PUBLISHED
Keywords: Audio Visual Speech Recognition, Region of Interest, Colour Based Segmen- tation, CUAVE database.